A sociology of comfort food in Singapore - Tan, Gee Kit (2018)
With there being limited research on the topic of comfort food in Singapore from the sociological perspective, this exploratory study aims to understand the type of comfort food Singapore Chinese youth aged between 21 years old and 34 years old consume amidst the evolving global food landscape. Purposive non-probability in-depth interviews and an online survey were conducted with 24 respondents of the Chinese ethnic group from November 2017 to January 2018. Using Claude Fischler’s theoretical framework of the omnivore’s dilemma, the analysis is broken down into two parts: (i) the identification of three categories of comfort food – home-cooked food, local food and non-local food and (ii) the effects of modern society on the respondents’ choice of comfort food from the three categories. The findings suggest that Singaporean Chinese youth lean towards non-local food as their comfort food to seek the cosmopolitan identity. However, this is an ideal as they still face neophobia in the reluctance of accepting fusion food.